A Systematic Review: Ethnomedicinal Uses And Pharmacological Activity Of Male Papaya Flower (Carica papaya L.) - Purwaningsih, Purwaningsih; Indrayudha, Peni (Universitas Muhammadiyah Surakarta, 2024)
An extensively utilized plant in traditional medicine is the papaya plant (Carica papaya L.). Papaya plants are useful in almost all parts, one part of (Carica papaya L.) that has potential is the papaya flowers. Papaya flowers are often used as a vegetable, but papaya flowers also have health benefits. The purpose of this review is to present thorough and current information on the ethnomedical usage and pharmacological activity of male papaya flowers. The search method was carried out using relevant keywords of the following databases: Google Scholar, ScienDirect, and NCBI. The results of the article search after going through the article selection process based on the database resulted in 25 relevant articles. Male papaya flowers contain many bioactive compounds known pharmacological activities, including antioxidant, anticancer, antibacterial, antidiabetic, analgesic, wound healing, antihyperlipidemic, bioinsecticide, tyrosinase inhibition and sun protection activity. This pharmacological activity may be caused by the large number of bioactive compounds contained in male papaya flowers.